A rhodamine-6G-based "turn-on" fluorescent probe for selective detection of Fe3+ in living cells. Issue 6 (21st January 2019) - Diao, Quanping; Guo, Hua; Yang, Zhiwei; Luo, Weiwei; Li, Tiechun; Hou, Dongyan
Abstract : A new fluorescent probe R6GES based on rhodamine 6G was designed and synthesized for the detection of Fe 3+ . Abstract : A new fluorescent probe R6GES based on rhodamine 6G was designed and synthesized for the detection of Fe 3+ . The Fe 3+ irreversibly binds to the R6GES and induces the ring opening and hydrolyzing of the spirolactam in the rhodamine unit. In the case of other biologically relevant metal ions, including Al 3+, Na +, K +, Li +, Ag +, Cu 2+, Mg 2+, Zn 2+, Co 2+, Fe 2+, Cd 2+, Ni 2+, Mn 2+, Ba 2+, Ca 2+ and Hg 2+, a negligible change was observed under similar conditions. These results indicate that probe R6GES can be used for the detection of Fe 3+ without interference from other competitive metal ions. The tested concentration range and the limit of detection (LOD) of the probe were 0–30.00 μmol L −1 and 0.030 μmol L −1, respectively. The present probe was applied to the determination of Fe 3+ in drinking water samples. The average recoveries ranged from 102.40% to 104.55% at a spiked concentration level of 20.00 μmol L −1, and the obtained results were consistent with those obtained using atomic absorption spectrometry (AAS). Furthermore, the fluorescent probe can also be applied as a bioimaging reagent for Fe 3+ detection in BEL-7402 cells.